International legal and economic-security aspects of protection of children's rights and their interests in the conditions of the legal regime of martial state - Сафончик, Оксана Іванівна; Сафончик, О. І.; Стефанчишен, Роман Володимирович; Стефанчишен, Роман Володимирович; Стефанчишен, Р. В.; Stefanchyshen, Roman V.; Глиняна, Катерина Михайлівна; Глиняна, К. М.; Hlyniana, Kateryna M. (Riga : Baltija Publishing, 2025)
This article identifies the key features of international legal and economic support for protecting children’s rights and interests under martial law. This is achieved by: determining the features of the legal regime of martial law that influence the guarantee of fundamental rights and freedoms in the state; outlining international legal standards for protecting children and their interests; and examining the economic and legal means of safeguarding children’s rights in Ukraine during a special period. The present study was conducted utilising a combination of general and special scientific cognition methods. The method of comparison was utilised in order to identify status rights during the period of the legal regime of martial law. The application of analytical methods enabled the identification of the quantitative and qualitative parameters that characterise the specifics of implementing certain measures at both the international and national levels for the protection of children's rights within the legal regime of martial law. The findings of the study have demonstrated that the implementation of the legal regime of martial law in Ukraine has precipitated directional changes to various types of social relations, which are objectively necessary for ensuring the state's sovereignty, territorial integrity, and overall existence. Concurrently, there are restrictions on some children's rights and an increased risk of violations and inadequate safeguards. In the context of martial law, economic support measures have been employed as a means of ensuring the rights of children are upheld. These measures encompass the allocation of financial assistance to children in the form of monetary payments, as well as the fulfilment of specific needs, which are met through the utilisation of state budgetary resources or through contributions from relevant specialised organisations, charitable foundations, and civil society institutions. Conclusion. The following proposals are hereby made: firstly, to deepen the involvement of such institutions in solving children's rights issues in the Ukrainian state through the activities of permanent observers monitoring the observance of children's rights in the territory recognised by international norms as the territory of Ukraine; and secondly, to implement a register of children who, as a result of martial law, require ongoing additional financial support (for the subsequent distribution of charitable aid to prevent speculation in this area).
Safonchyk O. International legal and economic-security aspects of protection of children's rights and their interests in the conditions of the legal regime of martial state / O. Safonchyk, R. Stefanchishen, K. Hlyniana // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. - Vol. 11(3). - Р. 51-59. URL: https://doi.org/10.30525/2256-0742/2025-11-3-51-59
Keywords: martial law; legal regime of martial law; restrictions on rights; protection of rights; children's rights; children's interests; international protection of children's rights; economic support; special period; financial assistance